PERANCANGAN FILM DOKUMENTER BERAS SOLOK NAGARI CUPAK KECAMATAN GUNUNG TALANG “SIPUTIH NAN TANAMO” - AYU ANDRIA, Dr. Syafwandi, M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
The lack of recognition and information about Rice Solok "Siputih Nan Tanamo" starting from the introduction of Regency of Solok, natural resources, the development of agricultural productivity, potential and cultural traditions contained therein been a major factor the authors make a documentary film Siputih Nan Tanamo, as well as the absence of documentary films related rice Solok "Nan Siputih Tanamo" to be exposed to the public. Through Documentary by designing social campaigns that it can easily provide information to the public with a visual depiction of a concept that is conveyed so as to provide an alternative viewpoint to the reality of the development of agricultural commodity Solok district and the whole dynamics in the general population. The message will be able to talk to expresif, including the values of social, cultural, economic, as well as the circumstances of Solok district. Documentary film form used isExpository, which aims to make the public more easily understand and know Rice Solok Tanamo and determine the potential contained therein. Besides the documentary will be supported by several other media that help the major mediato introduce the subject to the target audience that the movie poster, the CD cover and CD label, T-shirts, leaflets, Pin, Id-Card, stickers, cards, mugs and X-Banner , Data collection methods used were interviews, observation, documentation, books and internet.Metode data analysis were used that approach 5w + 1h that is what (what), who (who), when (when), where (in which), why (why) and how (how).Keywords: "Nan Siputih Tanamo" Documentary films